Визначення рівня екологічної безпеки системи «транспортний потік – дорога – придорожнє середовище» - Вайганг, Ганна; Римарук, Костянтин; Блажчук, Олена (Видавництво Львівської політехніки, 2015)
The method of estimating the environmental safety of the system "traffic flow - road - roadside environment" is given. The comprehensive assessment of environmental safety level determined by the individual, group and integrated environmental criteria in consideration of the impact of characteristics of elements of the system "traffic flow - road - roadside environment".
Determination of environmental safety of the system "traffic flow - road - roadside environment"